Is cold blood cardioplegia absolutely superior to cold crystalloid cardioplegia in aortic valve surgery? - Lerman, Daniel A. (2017)
BACKGROUND:Experimental evidence suggests that blood cardioplegia (BCP) may be superior to cold crystalloid cardioplegia (CCP) for myocardial protection. However, robust clinical data are lacking. We compared post-operative outcome of patients undergoing aortic valve replacement (AVR) using cold anterograde-retrograde intermittent BCP versus anterograde (CCP).METHODS:Adult consecutive isolated AVR performed between April 2006 and February 2011 at the Royal Infirmary Hospital of Edinburgh were retrospectively analyzed. The use of anterograde CCP was compared with that of intermittent anterograde-retrograde cold BCP. End points were intra-operative mortality, 30-day hospital re-admission, need for RBC or platelet transfusion, mechanical ventilation time and renal failure.RESULTS:Of total 774 cases analyzed, 592 cases of BCP and 182 cases of CCP were identified. Demographics did not differ between groups (mean patient age in years): 67±12 CCP and 69±12 BCP. Groups (BCP vs CCP) were indistinguishable (p > 0.05, NS) based on: average aortic cross clamp time (min) 77.01±14.47 vs 75.78±18.78, cardiopulmonary bypass time (min) 104.07±43.70 vs 100.34±25.90, surgery time (min) 190.53±61.80 vs 204.04±51.09 and post-operative total blood consumption (units) 1.38±2.11 vs 1.61±2.4. The percentage of patients who required platelets´ transfusion was similar: 12.8% BCP and 18.7% CCP (Fisher exact test, p=0.053). Prevalence of respiratory failure was lower in BCP than in CCP: 2.6% vs 6.3% (p=0.028). Admission time (days) at ICU was 3.63± 21.90 in BCP and 3.07 ± 8.04 in CCP (NS). Intra-hospital mortality, 30-day hospital re-admission, renal failure, sepsis, wound healing and stroke did not differ between groups.CONCLUSIONS:BCP was strictly not superior to CCP in every aspect. In particular it was definitely not superior in terms of post-operative ventricular function. Our results question the absolute superiority of BCP over CCP in terms of hard outcomes. Likelihood of serious complications should be considered to improve risk profile of patients before choosing a cardioplegic solution.